Stereoselective Synthesis of (4S,5S)-5-Vinyloxazolidin-2-one-4-carboxylate as a β-Vinylserine Synthetic Equivalent by Vinyl Grignard Addition to an N-Tosyl Version of Garner’s Aldehyde - Nolen, Ernest G.; Cao, Yuqi M.; Lewis, Brynn D.; Powers, Madison H.; Thompson, Andrew W.; Bennett, John M. (Synlett, 2021)
A highly efficient synthesis of a β-vinylserine synthetic equivalent is reported that exploits the stereodirecting effect of the N-toluenesulfonamide in an anti-diastereoselective (8.5:1) vinyl Grignard addition to an analogue of Garner’s aldehyde. Both aryl and alkyl Grignards are shown to give increased anti-selectivity compared with N-Boc Garner’s aldehyde.
Keywords: vinylserine; alkenyl amino acid; Garner aldehyde; oxazolidinones